Reassessing Banana Phylogeny and Organelle Inheritance Modes Using Genome Skimming Data - Wu, Chung-Shien; Sudianto, Edi; Chiu, Hui-Lung; Chao, Chih-Ping; Chaw, Shu-Miaw (Frontiers in Plant Science, 2021)
Bananas (Musa spp.) are some of the most important fruit crops in the world, contributing up to US10 billion in export values annually. In this study, we use high-throughput sequencing to obtain genomic resources of high-copy DNA molecules in bananas. We sampled 13 wild species and eight cultivars that represent the three genera (Ensete, Musa, and Musella) of the banana family (Musaceae). Their plastomic, 45S rDNA, and mitochondrial scaffolds were recovered from genome skimming data. Two major clades (Clades I & II) within Musa are strongly supported by the three genomic compartment data. We document, for the first time, that the plastomes of Musaceae have expanded inverted repeats (IR) after they diverged from their two close relatives, Heliconiaceae (the lobster-claws) and Strelitziaceae (the traveler’s bananas). The presence/absence of rps19 within IR regions reinforces the two intra-generic clades within Musa. Our comparisons of the bananas’ plastomic and mitochondrial DNA sequence trees aid in identifying hybrid bananas’ parentage. As the mitochondrial genes of Musa have elevated substitution rates, paternal inheritance likely plays an influential role on the Musa mitogenome evolution. We propose genome skimming as a useful method for reliable genealogy tracing and phylogenetics in bananas.